Artificially Linked Ubiquitin Dimers Characterised Structurally and Dynamically by NMR Spectroscopy. (24th June 2019) - Zhao, Xiaohui; Mißun, Maite; Schneider, Tobias; Müller, Franziska; Lutz, Joachim; Scheffner, Martin; Marx, Andreas; Kovermann, Michael
Abstract: As one of the most prevalent post‐translational modifications in eukaryotic cells, ubiquitylation plays vital roles in many cellular processes, such as protein degradation, DNA metabolism, and cell differentiation. Substrate proteins can be tagged by distinct types of polymeric ubiquitin (Ub) chains, which determine the eventual fate of the modified protein. A facile, click chemistry based approach for the efficient generation of linkage‐defined Ub chains, including Ub dimers, was recently established. Within these chains, individual Ub moieties are connected through a triazole linkage, rather than the natural isopeptide bond. Herein, it is reported that the conformation of an artificially K48‐linked Ub dimer resembles that of the natively linked dimer, with respect to structural and dynamic characteristics, as demonstrated by means of high‐resolution NMR spectroscopy. Thus, it is proposed that artificially linked Ub dimers, as generated by this approach, represent potent tools for studying the inherently different properties and functions of distinct Ub chains. Abstract : Synthetic substitute : An approach based on click chemistry for the targeted synthesis of artificially linked ubiquitin dimers has been explored. Structural and dynamic characterisation by means of NMR spectroscopy, accompanied by biochemical analysis, reveals the native‐like conformation and functionality of the dimers.